Pengukuran Indeks Masa Tubuh (IMT) untuk Penentuan Status Gizi Ibu Hamil di Posyandu Prima Desa Congkrang Kecamatan Muntilan Kabupaten Magelang - Eniyati Eniyati; Afi Lutfiyati; Ratna Prahesti; Reni Merta K (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2026)
Body Mass Index (BMI) is used as an indicator of a pregnant woman’s nutritional status and as a basis for recommendations on weight gain during pregnancy. A mother’s nutritional status before and during pregnancy can affect the growth of the fetus she is carrying (Ministry of Health of the Republic of Indonesia, 2019). If a mother's nutritional status is poor, either before pregnancy or during pregnancy, or if her Body Mass Index (BMI) is low, it has a negative effect on pregnancy outcomes, usually resulting in low birth weight (LBW) or preterm birth. Measuring BMI is a simple way to monitor the nutritional status of adults, especially regarding underweight and overweight issues. BMI is calculated based on body weight in kilograms (kg) divided by height in meters squared (m²). BMI is not related to gender and applies to adults (>18 years). The normal BMI threshold for Indonesia is 18.5–25.0. Mothers with body weight below the minimum are classified as "underweight," which puts them at risk of giving birth to malnourished babies. Fetuses experiencing malnutrition. Congenital defects in babies and premature birth. Likewise, a body weight above the normal range, referred to as 'overweight,' can increase the risk of gestational diabetes, preeclampsia, macrosomia in babies, or excess body weight. Based on the description above, it can be identified that measuring BMI is very important, especially for pregnant women. Community Service was carried out on October 4, 2025, from 09:00 to 12:00. The activity involved 6 facilitators with a total of 14 pregnant participants. Most respondents were of healthy reproductive age, totaling 11 people (78.5%). Most respondents had a primigravida obstetric status, totaling 9 people (64%). The majority of respondents had normal or above-normal Body Mass Index (BMI). There was 1 respondent with a low BMI.